THE EFFECT OF DUOLINGO IMPLEMENTATION ON SEVENTH-GRADE STUDENTS’ VOCABULARY MASTERY - Dewi, Ni Putu Adis Cantika; Santosa, Made Hery; Dewi, Kadek Sinthya (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2025)
Mastering vocabulary is important in order to elevate English skills in every aspect (Reading, Listening, Speaking, Writing). In learning a language, a strong fundamental of vocabulary knowledge is needed. However, it seems difficult to learn English if students do not master the vocabulary. Based on preliminary observations by researchers at Public Junior High School in North Bali, researcher found that most students' vocabulary skills did not meet the standards set by the school curriculum. The purpose of this study is to determine the impact of Duolingo on the vocabulary skills of 7th-grade students in Public Junior High School In North Bali. The researcher wants to know and investigate whether the use of Duolingo has a significant effect on the vocabulary skills of 7th-grade students by comparing two different groups. One group got treatment by implementing Duolingo in the learning process, while the other group did not receive treatment. This study used an explanatory sequential mixed method design using The post-test of quasi-experimental design. The results of this study showed that the average score in the experimental class from the post-test value is higher than the control group. From the paired t-test result, it is shown that sig.2 tailed of 0.000 <0.05 which indicates that using Duolingo does affect students’ vocabulary mastery